The Ability To Find the Main Idea in Paragraphs with the Scaffolded Reading Method Based on the Student Motivation - Yani, Juli; Apriyani, Sari (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study is entitled The Ability to Find Main Ideas in Paragraphs with the Scaffolded Reading Method Based on Student Reading Motivation in Class XI SMP Negeri 2 Balaraja. This research was motivated by: 1) the existence of various facts that show that students' reading comprehension ability and reading motivation are low; 2) The ability to find the main idea in a paragraph is very important in an effort to understand a reading text. This study was conducted to determine the effect of the motivation-based Scaffolded Reading method on improving the ability of student learning outcomes in finding the main idea in paragraphs. The research was conducted in class IX-C SMPN 2 Balaraja. The method used in research is an experimental method with a quantitative approach. After knowing the results of data analysis that the application of the scaffolded reading method is effective in improving the ability to find the main idea in paragraphs, then it is better in learning reading comprehension this technique.